A Short Review on Developing Technologies by Hydrogen - Norazlianie, Sazali (Akademia Baru Publishing (M) Sdn Bhd, 2019)
Hydrogen is deemed as the most significant fuel of the future, with strong potential to minimise pollution. Hence, there is also growing global interest in reducing the effects of greenhouse gases as well as other pollutant gases. In order to explore the implementation of hydrogen as a fuel or energy carrier, it requires an easily acquired broad-spectrum knowledge on a variety of processes as well as their advantages, disadvantages, and potential adjustments in making a process suitable for future development. Aside from directly utilising the hydrogen produced from these processes in fuel cells, hydrogen-rich streams can also be used to generate high-value of ethanol, methanol and gasoline, as well as other high-value chemicals. This paper presented a brief overview on the remarkable current and emerging hydrogen technologies.